Kemitraan Pendidikan Anak Usia Dini (Sinergi Tiga Pilar Pendidikan: Keluarga, Sekolah dan Masyarakat) - Jamilah Jamilah; Jamilah (SIMULACRA: JURNAL SOSIOLOGI, 2019)
The purpose of this study is to describe the partnership of early childhood education between school families and the community. This type of research was a qualitative deskriptif approach. The research subjects were parents, educators and managers.  Data were collected through interviews, observation, and document study. The data were analyzed using the qualitative analysis techniques data collecting, data display and conclusion drawing. The results showed that the relationship of partnerships and cooperation between PAUD institutions and parents and the community of students can be achieved to the maximum and increase the role of parents of early childhood and the community in the implementation of early childhood education institution programs.